Study of prescription pattern of topical antimicrobials used for eye infections in ophthalmology - Khan, Mariya P.; Khandelwal, P. N.; Kishore, Chitrita; Singh, Anushka (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The use of topical antibacterial medicines for the treatment of patients with infections in the eye has various advantages with some disadvantages. After literature search, I was unable to find a larger number of articles on eye infections, so I selected this study in this particular area. Methods: It was observational cross-sectional study; 270 patients were enrolled who visited the Ophthalmology OPD with a diagnosis of eye infections. Results: The mean age±SD were 39.53 (±16.30). The 40.37% patients were suffering from conjunctivitis. The most commonly prescribed dosage forms were eye drops 38.58% and eye ointment 30.37%. The medicines prescribed by generic name were 37.47% and by brand name 62.52%. Conclusions: Total drugs prescribed were 451. Price variation of drugs is calculated by comparing the price of generic vs. branded drugs.